Preliminary Study: Project-Based Learning with Chamilo e-learning in Junior High School Physics Education - Islamia, Saribatul; Rahmad, M.; Yennita, Y (Jurnal Ilmiah Pendidikan Fisika, 2025)
Implementing Project-Based Learning (PjBL) is an effective strategy for enhancing 21st-century skills. Integrating technology through Chamilo e-learning facilitates more interactive and engaging digital learning. This study aims to analyze the implementation of the Chamilo e-learning-assisted PjBL model in schools and assess teachers' and students' confidence in its application. This research employs a survey method with random sampling involving five science teachers and 60 students. Data were collected through a questionnaire validated for reliability (KR-20 coefficient: 0.82 for teachers, 0.77 for students), covering three key aspects: (1) PjBL implementation in schools, (2) Chamilo e-learning utilization, and (3) the effectiveness of Chamilo e-learning-assisted PjBL in enhancing students' creative thinking and digital literacy. Data analysis was conducted using a descriptive quantitative approach by calculating percentages for each measured aspect. The findings indicate that the Chamilo e-learning-assisted PjBL model is rarely implemented in schools. Most teachers have not applied this model to enhance students' creative thinking and digital literacy due to their limited understanding of PjBL and Chamilo e-learning. Furthermore, 100% of students reported never having learned using this model. The confidence level of teachers regarding the need for implementing Chamilo e-learning-assisted PjBL reached 80%, while students' confidence level was 88.5%. These results highlight the urgent need for systematic interventions to enhance the application of Chamilo e-learning-assisted PjBL in science education. This study suggests continuous teacher training to improve their competency in utilizing this model. Moreover, schools must ensure sufficient technological infrastructure and stable internet access to support its effective implementation, ultimately fostering students' creative thinking and digital literacy skills.